Dual-Conditioning of Sludge using Chitosan and Metal Cations - Lau, Shiew Wei; Tang, S.D.; Ang, Ming; Sen, Tushar; Chua, Han Bing (Singapore International Water Week - Water Convention, 2014)
Sludge dewatering is important in sludge management and disposal. In practice, chemical conditioners are often introduced to aid sludge dewatering. This study investigated the simultaneous application of chitosan and metal cations as dual-conditioners to improve sludge dewaterability. The dewatering performance of sludge was evaluated using three common measurements i.e. the capillary suction time (CST) test, specific resistance to filtration (SRF) test, and moisture content of the filtered sludge cake. The effectiveness of metal cation in sludge conditioning and dewatering was found in an ascending order of Na+ < K+ ≈ Mg2+ < Ca2+ < Al3+ < Fe3+. Dual-conditioning using chitosan and metal cation further enhanced sludge dewaterability in a similar manner. Cations may have significant effects on sludge conditioning by neutralisation of the negative surface charges, bridging of the floc components and salting out effect, leading to improved dewaterability when used in conjunction with chitosan.